Carbon/montmorillonite hybrids with different activation methods: adsorption of norfloxacin - Zelaya Soulé, María Emilia (2019)
Within the group of emerging pollutants, antibiotics have raised scientific concern due to, among others, their negative influenceon the health of living beings. To investigate the adsorption capacity of the antibiotic norfloxacin (NFX), in this workcarbon/montmorillonite hybrid materials (MD) obtained by hydrothermal synthesis using dextrose as carbon source, withacid and thermal activation methods, as well as some precursor materials, were deeply characterized. The characterizationresults of MD showed the presence of carbon at both the interlayer and external surfaces of montmorillonite (M), with anincrease of more than three times in the specific surface area and also in the negative surface electrical charge with respectto M sample. The MD materials assayed were effective (around 40%) to remove NFX from aqueous medium at pH 7, theremoval efficiency being within that of the M (75?99%) and hydrothermal carbon (5%) samples. The XRD and zeta potentialvalues of NFX adsorbed products indicated that, while in M sample the interlayer is the preferential adsorbing surface, forthe MD material assayed (activated with higher acid concentration) the external surface would be the more active.